2022
DOI: 10.15252/embr.202153684
|View full text |Cite
|
Sign up to set email alerts
|

FACT maintains nucleosomes during transcription and stem cell viability in adult mice

Abstract: Preservation of nucleosomes during replication has been extensively studied, while the maintenance of nucleosomes during transcription has gotten less attention. The histone chaperone FACT has a role in transcription elongation, although whether it disassembles or assembles nucleosomes during this process is unclear.To elucidate the function of FACT in mammals, we deleted the Ssrp1 subunit of FACT in adult mice. FACT loss is lethal, possibly due to the loss of the earliest progenitors in bone marrow and intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(105 reference statements)
2
5
0
Order By: Relevance
“…The amount of FACT-dependent mRNA transcription (both stimulated and repressed) are largely consistent between our data and experiments performed in S. cerevisiae (Feng et al, 2016), ES cell lines (F. Chen et al, 2020), and in a mouse model (Goswami et al, 2022), suggesting conservation of FACT function throughout eukaryotes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The amount of FACT-dependent mRNA transcription (both stimulated and repressed) are largely consistent between our data and experiments performed in S. cerevisiae (Feng et al, 2016), ES cell lines (F. Chen et al, 2020), and in a mouse model (Goswami et al, 2022), suggesting conservation of FACT function throughout eukaryotes.…”
Section: Discussionsupporting
confidence: 88%
“…As many groups have suggested, the act of transcription by RNAPII itself may be responsible for destabilization of nucleosomes, creating a genomic conflict for FACT to resolve (Farnung et al, 2021; Formosa & Winston, 2020; Goswami et al, 2022; Célia Jeronimo et al, 2020; Y. Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the mouse with deletion of the Ssrp1 gene could not survive to adulthood, and loss of SSRP1 reduces the viability of stem cells in several tissues. 53 , 54 We analyzed the effect of SSRP1-Q265K mutation on the growth and pluripotency of mESCs. We first cultured wild-type and Ssrp1 Q265K mESCs in the standard SL2i medium, which contains serum (S), leukemia inhibitory factor (L), and two inhibitors (2i) that inhibit GSK3β (GSKi) and MEK1/2 (MEKi), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…FACT also plays a role in suppressing cryptic transcription ( 9 , 10 ), silencing heterochromatin ( 11 , 12 ), and inhibiting expression of subtelomeric genes and MERVL retrotransposon ( 13 , 14 , 15 , 16 ). Intriguingly, FACT is abundantly expressed in undifferentiated or tumor cells, while it has very limited expression in differentiated cells, suggesting possible involvement in maintenance of undifferentiated cell status ( 17 , 18 , 19 ). Substantial progress has been made in understanding the structural features of FACT and its roles in development and carcinogenesis ( 20 , 21 , 22 ).…”
mentioning
confidence: 99%